Do budget balance rules anchor budget balance expectations? – Some international evidence - Jan-Christoph Rülke; Michael Frenkel; Eliza Lis (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This is the first study that analyzes whether budget balance expectations are anchored and whether budget balance rules effectively anchor expectations. To this end, we use a unique data set which covers budget balance expectations in 17 countries that implemented a budget balance rules. While our results are mixed concerning the general impact of budget balance rules on anchoring expectations, we do find that specific features of budget balance rules are important to successfully anchor budget balance expectations.
Keywords: H62; H68; H11; 330